How specialists can be generalists: resolving the "parasite paradox" and implications for emerging infectious disease - Agosta,Salvatore J. (2010)
The parasite paradox arises from the dual observations that parasites (broadly construed, including phytophagous insects) are resource specialists with restricted host ranges, and yet shifts onto relatively unrelated hosts are common in the phylogenetic diversification of parasite lineages and directly observable in ecological time. We synthesize the emerging solution to this paradox: phenotypic flexibility and phylogenetic conservatism in traits related to resource use, grouped under the term ecological fitting, provide substantial opportunities for rapid host switching in changing environments, in the absence of the evolution of novel host-utilization capabilities. We discuss mechanisms behind ecological fitting, its implications for defining specialists and generalists, and briefly review empirical examples of host shifts in the context of ecological fitting. We conclude that host shifts via ecological fitting provide the fuel for the expansion phase of the recently proposed oscillation hypothesis of host range and speciation, and, more generally, the generation of novel combinations of interacting species within the geographic mosaic theory of coevolution. Finally, we conclude that taxon pulses, driven by climate change and large-scale ecological perturbation are drivers of biotic mixing and resultant ecological fitting, which leads to increased rates of rapid host switching, including the agents of Emerging Infectious Disease.